Influence of Supply Chain Integration, IT Practices and Visibility on Modular Design and Supply Chain Agility, supported Maritime and Tourism Business in Indonesia - Nyoman Sudapet; Agus Sukoco; Muhammad Ikhsan Setiawan (International Journal of Supply Chain Management, 2019)
Present study aims to examine the relationship between supply chain integration, and IT capability on the supply chain agility in the banking sector of Indonesia, support Maritime and Tourism Business. Moreover, impact of supply chain visibility is examined on supply chain modular design and supply chain agility. The current research aims to analyse the nature of relationships among latent variables; therefore, this study chose the latent analysis technique for investigating these relationships. Statistical Package for Social Sciences (SPSS) and Partial Least Squares Structural Equation Modelling (PLS-SEM) were employed to describe the data and the relationship among variables, respectively. The p-values in the result show that all the under-study variables show significant results while the result of relationship between IT practices and supply chain agility is insignificant. The study provides a comprehensive framework in context of supply chain agility and supplier’s modular design. The literature fills the theoretical gap in existing literature and join the supply chain integration and IT practices with supply chain agility and connects supply chain visibility with supplier’s modular design. This study is helpful for the policy makers of the banking sector of Indonesia in strategizing the ways to impact the agility in their supply chain process.